2019
DOI: 10.1108/mij-10-2019-0005
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Chlorpromazine and deep venous thrombosis

Abstract: Purpose Since the development of antipsychotic drugs in the 1950s, a variety of studies and case reports have been published that suggest an association between exposure to typical antipsychotics and venous thromboembolisms (VTE). Therefore, when starting treatment with antipsychotics, especially low-potency typical antipsychotics and clozapine, health-care providers must account for the patient’s existing VTE risk factors. Design/methodology/approach In this case report, the authors describe the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…Possible underlying mechanisms include platelet dysfunction [ 2 , 3 , 13 ], immunomodulatory and proinflam-matory effects, and metabolic syndrome associated with antipsychotic drugs [ 14 ]. Because of clozapine’s strong affinity for 5HT 2a receptors (at least 10 times stronger than for D2 receptors), 5HT 2a -induced platelet aggregation leading to thromboembolism has also been hypothesized [ 6 , 15 ]. In addition, clozapine often leads to sedation as a side effect, which may contribute to immobility and venous stasis [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Possible underlying mechanisms include platelet dysfunction [ 2 , 3 , 13 ], immunomodulatory and proinflam-matory effects, and metabolic syndrome associated with antipsychotic drugs [ 14 ]. Because of clozapine’s strong affinity for 5HT 2a receptors (at least 10 times stronger than for D2 receptors), 5HT 2a -induced platelet aggregation leading to thromboembolism has also been hypothesized [ 6 , 15 ]. In addition, clozapine often leads to sedation as a side effect, which may contribute to immobility and venous stasis [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, numerous case reports and studies have shown an increased risk of VTE with antipsychotic use. For example, a 51-year-old female patient with bipolar disorder developed a pulmonary embolism following chlorpromazine treatment, while instances of central retinal vein occlusion have been observed in patients administered olanzapine and risperidone [36,37]. Furthermore, a case of a 39-year-old woman with chronic schizophrenia who developed acute right hemiparesis and visual field loss during a switch to clozapine therapy has been reported, leading to a provisional diagnosis of ischemic stroke [38,39].…”
Section: Mostly Involved Antipsychotic Medicationsmentioning
confidence: 99%